Gender, loss, and the erosion of bodily capital: A study with women diagnosed with late stage breast cancer. Issue 7 (3rd October 2022) - Quinn, Sarah; Mcclelland, Sara I.; Gerber, Lynne
ABSTRACT: To learn about the gendered experience of bodily loss, this paper analyzes interviews with women diagnosed with metastatic breast cancer (N = 32). Across the interviews, we find that specific bodily sites – hair, breast(s), thinness – and the gender norms associated with these sites do not loosen their grip near the end of life, but rather constitute meaningful sites of loss. Interviews demonstrate that when women lose a valued physical characteristic they also feel the loss of gendered statuses associated with that aspect of the body. We theorize the resulting emotional experience as positionality grief, or sorrow over an injured sense of self and that is tied to a sense of lowered place on social hierarchies. For feminist scholars, our study links women's complex desires with their particular forms of embodiment that delimit spaces of possibility in the social world. For Bourdieusian scholars, our study calls attention to the importance of focusing not just on the acquisition, but the loss of embodied capital in social life. The implications of these bodily changes, therefore, structure how women grapple with gender and sexuality over the course of their lives.